Arabs' contribution to the art of translation - Arif Karkhi Abukhudairi (Journal of Modern Languages)
As shown through this paper, Arabs made great endeavors in the field of translation, and they succeeded in transferring the treasures of foreign thought such as Greek, Persian, Hindi, European and others into Arabic. Besides, they preserved the Greek heritage and added to it their own ideas and theories. Moreover, they managed to invent new and valuable sciences and scientific methods upon which the Europeans built their present civilization.